Boozy brunch : the quintessential guide to daytime drinking - Joseph, Peter, 1982- (Taylor Trade Pub., 2012)
"With Boozy Brunch, you have your pick of more than one hundred eye-opening drink recipes and twenty-five food pairings, with entertaining drink histories and liquor-laden quotes from the famous and infamous. The first book of its kind, Boozy Brunch offers brunchy alternatives and revved-up variations to the classic set of champagne-based, coffee-based, or fruit or vegetable juice-based cocktails that will help you make the most of your brunch. Plus, you'll find a set of hangover cures for those still recovering from the night before"--